Assessing Socket Fit Effects on Pressure and Shear at a Transtibial Residuum/Socket Interface - Kirstie M. Devin; Jinghua Tang; David Moser; Liudi Jiang (Applied Bionics and Biomechanics)
Fluctuations in residuum volume during daily activities are known to occur in lower-limb amputees. This can cause frequent changes to fit, which cannot be accommodated by commonly-used prosthetic sockets. The real-time effects, if any, of these minor socket fit changes on interface biomechanics have not been studied extensively. Amputees commonly use different layers of socks to accommodate frequent volume fluctuations, enabling adjustment of socket fit. We, thus, altered socket fit levels via addition/removal of sock layers to a transtibial amputee who habitually-donned two-sock layers to mimic relatively looser and tighter socket fits. Interface pressure and shear sensors were placed at known prominent load-bearing sites of the transtibial residuum/socket interface, i.e., patellar tendon (PT), popliteal fossa (PF), and anterior–distal (AD) end, to measure real-time biomechanical interactions during standing and level walking. Although socket fit level was only slightly modified, changes in interface pressure and shear across anatomical sites were still observed. Tighter fit corresponds to notable pressure reduction at AD during early stance and pressure increase at PT during terminal stance due to the residuum being pushed up. Shear-to-pressure ratios were used to assess comfort, while pressure– and shear–time integrals were used to assess tissue health. We observed more notable changes at tissue sites (e.g., AD and PF). Combined evaluation of pressure and shear, including shear-to-pressure ratio and time integrals, may offer insight for residuum care.